(untitled) (Journal of the College of Basic Education, 2022)
The global population increase and the increase in development requirements have led to the consumption of electrical energy that is produced from electric power plants that use fossil fuels, which led to climate changes represented by global warming due to greenhouse gases and sustainable development, which in turn leads to higher temperatures, which affects the basic elements of human life such as The environment and the increase in energy demand rates, and research shows that nuclear technology is sufficient for the purpose, and this requires the establishment of reactors that are of the highest levels of safety and security, less waste generation and have little economic efficiency, and this reduces dependence on fossil fuels and research shows that Europe consumes 5104 (terawatt / hour) in 2010 and is expected 8493 (terawatt / hour) for 2050. Availability of requirements for owning nuclear power plants, including preparing researchers and specialized workers, teaching nuclear science in universities, spreading cultural and nuclear awareness for workers and the public, and having a regulatory body with experience in monitoring the operation of nuclear power plants